2013
DOI: 10.3390/molecules181215064
|View full text |Cite
|
Sign up to set email alerts
|

Multicomponent Click Synthesis of New 1,2,3-Triazole Derivatives of Pyrimidine Nucleobases: Promising Acidic Corrosion Inhibitors for Steel

Abstract: A series of new mono-1,2,3-triazole derivatives of pyrimidine nucleobases were synthesized by one-pot copper(I)-catalyzed 1,3-dipolar cycloaddition reactions between N-1-propargyluracil and thymine, sodium azide and several benzyl halides. The desired heterocyclic compounds were obtained in good yields and characterized by NMR, IR, and high resolution mass spectrometry. These compounds were investigated as corrosion inhibitors for steel in 1 M HCl solution, using electrochemical impedance spectroscopy (EIS) te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
22
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 61 publications
(80 reference statements)
5
22
0
3
Order By: Relevance
“…The impedance technique can provide more detailed information about the interfacial properties of surface-modified electrodes [35]. In this experiment, two methods of CV and electrochemical impedance spectroscopy (EIS) were used to monitor the fabricating process of the modified electrode, and the results are presented in Fig.…”
Section: Electrochemical Property Of Cs@al 2 O 3 @Go Film-modified Gcementioning
confidence: 99%
“…The impedance technique can provide more detailed information about the interfacial properties of surface-modified electrodes [35]. In this experiment, two methods of CV and electrochemical impedance spectroscopy (EIS) were used to monitor the fabricating process of the modified electrode, and the results are presented in Fig.…”
Section: Electrochemical Property Of Cs@al 2 O 3 @Go Film-modified Gcementioning
confidence: 99%
“…A new 1,2,3‐triazole derivative of pyrimidine nucleobases was reported via a Cu(I)‐catalysed one‐pot three‐component click reaction involving 1,3‐dipolar cycloadditon with N‐1 propargylpyrimidine nucleobases (Scheme ) . The reaction involved monopropargyl nucleobases, sodium azide and several benzyl halides in presence of Cu(OAc) 2 ⋅ H 2 O in EtOH/H 2 O (2 : 1 v/v) at room temperature for 24 h to afford 1,4‐disubstituted 1,2,3‐triazole nucleobases.…”
Section: Synthesis Of Heterocyclesmentioning
confidence: 99%
“…Bonnamour et al have reported a consecutive threecomponent synthesis of trifluoromethyltriazole derivatives 22 as pseudopeptide based upon this concept (Scheme 14). [59,60] The concept of in situ azide generation has also been employed for the generation of 8-trifluoromethylquinoline-based 1,2,3-triazoles derivatives 25 for the evaluation of their in vitro antimicrobial activity. [54] CF 3 -containing derivatives, modifying the biological activity of a system, [55] have acquired significance, particularly in the field of peptidomimetics.…”
Section: Azide Formation Via Nucleophilic Aliphatic Substitutionmentioning
confidence: 99%